Novel recurrently mutated genes and a prognostic mutation signature in colorectal cancer. Issue 4 (20th June 2014) - Yu, Jun; Wu, William K K; Li, Xiangchun; He, Jun; Li, Xiao-Xing; Ng, Simon S M; Yu, Chang; Gao, Zhibo; Yang, Jie; Li, Miao; Wang, Qiaoxiu; Liang, Qiaoyi; et al.
Abstract : Background: Characterisation of colorectal cancer (CRC) genomes by next-generation sequencing has led to the discovery of novel recurrently mutated genes. Nevertheless, genomic data has not yet been used for CRC prognostication. Objective: To identify recurrent somatic mutations with prognostic significance in patients with CRC. Method: Exome sequencing was performed to identify somatic mutations in tumour tissues of 22 patients with CRC, followed by validation of 187 recurrent and pathway-related genes using targeted capture sequencing in additional 160 cases. Results: Seven significantly mutated genes, including four reported ( APC, TP53, KRAS and SMAD4 ) and three novel recurrently mutated genes ( CDH10, FAT4 and DOCK2 ), exhibited high mutation prevalence (6–14% for novel cancer genes) and higher-than-expected number of non-silent mutations in our CRC cohort. For prognostication, a five-gene-signature ( CDH10, COL6A3, SMAD4, TMEM132D, VCAN ) was devised, in which mutation(s) in one or more of these genes was significantly associated with better overall survival independent of tumor-node-metastasis (TNM) staging. The median survival time was 80.4 months in the mutant group versus 42.4 months in the wild type group (p=0.0051). The prognostic significance of this signature was successfully verified using the data set from the Cancer Genome Atlas study. Conclusions: The application of next-generation sequencing has led to the identification of three novel significantly mutated genes in CRC and a mutation signature that predicts survival outcomes for stratifying patients with CRC independent of TNM staging.